Relationship between slack resources and performance: temporal symmetry and duration of effects - Maria Augusti-Perez; José Luis Galán González; Francisco J. Acedo (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose Although slack resources and their relationship to performance have been widely studied in the literature, the temporal symmetry of this relationship, and the duration of its effects, are still unknown aspects and are the objective of this paper. Design/methodology/approach To evaluate this effect, an exploratory study has been designed on a sample of 449 Spanish industrial companies over a period of 12 years, assessing the impact of idle resources on economic and financial profitability. By means of hierarchical regressions, the short- term, medium- term and long-term effects of slack resources have been evaluated. Findings The results show that the impact on performance depends on the type of resource considered. Available slack has a consistent and positive effect on economic profitability in the short term. Other types of slack show persistent effects on performance, but, in the case of the recoverable slack, with a negative sign that contradicts the benefits provided by these resources. Finally, potential slack only has a permanent effect on financial profitability, but the sign changes depending on the economic context under consideration. There are also differences in the duration of the effects according to the type of resources. Originality/value This paper advances the knowledge about the slack-performance relationship over time that has been scarcely studied.
Keywords: 650; Performance; Slack; Timing; Industrial companies; Temporal symmetry